Comparing the use of meat and clay during cutting and projectile research. (1st April 2018) - Key, Alastair; Young, Jesse; Fisch, Michael R.; Chaney, Morgan E.; Kramer, Andrew; Eren, Metin I.
Highlights: Clay's reliability as a meat proxy in cutting and projectile research is examined. Each material displays distinct cutting mechanics and resistance to edges. Projectile tests confirmed meat to provide greater resistance to penetration. Displacement and work of impact and force were dependent on projectile size. Clay is not an accurate proxy for meat, but can be useful in specific conditions. Abstract: Diverse disciplines investigate how muscular tissue (i.e. 'meat') responds to being cut and deformed, however, large-scale, empirically robust investigations into these matters are often impractical and expensive. Previous research has used clay as an alternative to meat. To establish whether clay is a reliable proxy for meat, we directly compare the two materials via a series of cutting and projectile tests. Results confirm that the two materials display distinct cutting mechanics, resistance to penetration and are not comparable. Under certain conditions clay can be used as an alternative to meat, although distinctions between the two may lead to experimental limitations.